Integrasi Paradigma Teori Belajar dalam Praktik Pembelajaran Kontemporer pada Madrasah Aliyah - Nahdliana Aisyatul Asyiroh; Samsul Susilawati; Nurlaeli Fitriah (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2026)
The development of digital technology, educational transformation, and shifting learning paradigms have driven the need for more adaptive pedagogical approaches in Madrasah Aliyah, yet studies on learning theory within Islamic education remain fragmented and have not produced a comprehensive integrative framework. This study aims to analyze the characteristics of various learning theory paradigms, examine their relevance to contemporary learning, and formulate an integrative framework for applying these paradigms in Islamic Religious Education (PAI) practice at Madrasah Aliyah. The study employs a qualitative approach using the library research method, drawing data from 22 scholarly articles and other academic sources published between 2021 and 2026, analyzed through content analysis techniques. The findings show that the paradigms of behaviorism, cognitivism, constructivism, humanism, and social learning theory remain relevant in explaining contemporary learning processes, as summarized in a comparative matrix of the paradigms. Learning practices in Madrasah Aliyah demonstrate the integration of these five paradigms through project-based, problem-based, collaborative, and differentiated learning, as well as digital technology use, with implications for developing more adaptive and contextual PAI teaching methods and media. The novelty of this study lies in its integrative conceptual framework that explicitly connects five learning theory paradigms with the context of PAI learning at the Madrasah Aliyah level, a scope not yet comprehensively addressed in prior conceptual research. Accordingly, the integration of learning theory paradigms can serve as a conceptual foundation for designing learning that balances students' cognitive, affective, psychomotor, and spiritual development in line with the demands of Islamic education in the digital era.